Penentuan Total Flavonoid Content (TFC) dan Aktivitas Antioksidan Tumbuhan Insulin (Smallanthus sonchifolius): Determination of Total Flavonoid Content (TFC) and Antioxidant Activity of Insulin Plants (Smallanthus sonchifolius) - Erwin, Erwin; Febrianti, Irna; Pasaribu, Subur P.; Aziz, Abdul (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2024)
Smallanthus sonchifolius or known by the local name Insulin or Yacon is a traditional medicinal plant commonly used to treat diabetes. Apart from being a diabetic drug, insulin also has the potential to have antioxidant, anticancer, and anti-melanogenic activities. The aim of the study was to determine total flavonoid content (TFC) and DPPH radical scavenging of Insulin bark and stem wood extracts using UV-Vis spectrometry. The calculation results show that the total flavonoid content equivalents to quercetin in Insulin bark and stem wood extracts is 29.2 and 210.2 mg QE/g extract, respectively, while the DPPH radical scavenging test results are 80.01 and 58.85 ppm, respectively. Both the TFC and the antioxidant properties of the stem wood extract were higher than that of the Insulin bark extract. Keywords: Smallanthus sonchifolius, insulin, TFC, traditional medicine Abstrak Smallanthus sonchifolius atau dikenal dengan nama lokal Insulin atau Yacon adalah tanaman obat tradisional yang biasa digunakan untuk pengobati penyakit diabetes. Selain sebagai obat diabetic, Insulin juga berpotensi memiliki aktivitas antioksidan, antikanker, dan anti-melanogenik. Tujuan penelitian adalah untuk menentukan total flavonoid content (TFC) dan peredaman radikal DPPH dari ekstrak kulit dan kayu batang Insulin menggunakan spektrometri UV-Vis. Hasil perhitungan menunjukkan total flavonoid content yang setara dengan quarcetin pada ekstrak kulit dan kayu batang Insulin adalah 29,2 dan 210,2 mg QE /g ekstrak, secara berturut-turut, sedangkan hasil uji peredaman radikal DPPH adalah 80,01 dan 58,85 ppm, secara berturut-turut. Baik TFC maupun sifat antioksidan ekstrak kayu batang lebih tinggi dibandingkan dengan ekstrak kulit batang Insulin. Kata Kunci: Smallanthus sonchifolius, insulin, TFC, obat tradisional